1988
DOI: 10.1523/jneurosci.08-11-04239.1988
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic growth and remodeling of cat retinal ganglion cells during fetal and postnatal development

Abstract: We have studied the development of retinal ganglion cell morphology in the cat's visual system from early fetal to postnatal times. In particular, we have examined the contribution of growth and remodeling to the establishment of mature retinal ganglion cell form. Ganglion cells were identified by retrograde labeling with rhodamine latex microspheres deposited in the superior colliculus and lateral geniculate nucleus between embryonic day 34 (E34; birth = E65) and adulthood. To reveal the fine morphological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
157
1
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 47 publications
(108 reference statements)
13
157
1
1
Order By: Relevance
“…First, we describe the time course of beta cell dendritic stratification in the central and * Distinct classes of RGCs could be recognized in retinal wholemounts by ESO, some 2 weeks before birth. This is in accord with the results of Ramoa et al (1988) who examined the morphological development of fetal cat RGCs labeled by intracellular injection of Lucifer yellow. As may be seen in Figure 1, beta cells could be readily distinguished from other RGC classes by their relatively short, bushy dendrites branching in close proximity to the cell body.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…First, we describe the time course of beta cell dendritic stratification in the central and * Distinct classes of RGCs could be recognized in retinal wholemounts by ESO, some 2 weeks before birth. This is in accord with the results of Ramoa et al (1988) who examined the morphological development of fetal cat RGCs labeled by intracellular injection of Lucifer yellow. As may be seen in Figure 1, beta cells could be readily distinguished from other RGC classes by their relatively short, bushy dendrites branching in close proximity to the cell body.…”
Section: Resultssupporting
confidence: 90%
“…RGCs with dendrites that stratify in the inner portion of the IPL signal information about increments of light, while those with dendrites stratifying in the outer portion of the IPL signal light decrements (Famiglietti and Kolb, 1976;Nelson et al, 1978). Whereas in the mature cat retina the dendrites of ON and OFF alpha and beta RGCs are unistratified, early in development the dendritic processes of these neurons have been noted to ramify throughout the IPL (Maslim and Stone, 1988;Dann et al, 1988;Ramoa et al, 1988). Although, the precise time course of the stratification process has yet to be determined, it has been reported in the developing cat retina that this occurs around the time that bipolar cells form synapses in the IPL (Mashm andStone, 1986, 1988).…”
mentioning
confidence: 99%
“…SLDPs emanate from the dendritic shaft and show pleomorphic morphological features, including filiform structures distinct from the dendritic spines in adults (e.g., Morest, 1969;Scheibel et al, 1973). They also transiently increase in number at an early stage of development (e.g., Morest, 1969;Scheibel et al, 1973;Lund et al, 1977;Boothe et al, 1979;Garey and Saini, 1981;Hammer et al, 1981;Phelps et al, 1983;Dvergsten et al, 1986;Ramoa et al, 1988). These in vivo findings suggest that SLDPs are continuously remodeled in development.…”
mentioning
confidence: 88%
“…In the retina, ganglion cells go through a transient phase with profuse branching and an excessive number of spine-like dendritic processes (cat: Dann et al, 1988;Ramoa et al, 1988;rat: Yamasaki and Ramoa, 1993;hamster: Lau et al, 1992b). It has been suggested that these spine-like processes are the initial targets for synaptic input from bipolar and amacrine cells, but this has not been confirmed at the ultrastructural level (Wong et al, 1992).…”
Section: Development Of Glutamatergic Circuitry In the Iplmentioning
confidence: 99%